USING BLOCKCHAIN TECHNOLOGY TO IMPROVE CREDIT RISK MANAGEMENT: "A survey study of a sample of academics and professionals in public universities" - Ismail, Basheer; Ramo, Wahid (Humanities Journal of University of Zakho, 2024)
The current study aims to clarify Blockchain technology, the areas that can be applied to, the use of this technology in developing accounting systems and increasing the quality of accounting information to facilitate the decision-making process related to granting credit. Further, the role of Blockchain Blockchain technology in future forecasts and improving credit risk management is demonstrated. To achieve the objectives of the study, a pragmatic approach that mixes the inductive and deductive approaches was adopted to discuss the basics of Blockchain technology and its most important accounting effects by designing a Blockchain network dedicated to predicting financial failure models for companies and applying the Altman Z score model to (10) private joint-stock companies listed in the Iraq Stock Exchange. Hence, a questionnaire is designed to take the opinions of academics and professionals from lecturers working in Iraqi public universities and the Kurdistan Region. The results concluded that there is an impact of Blockchain technology in improving credit risk management. This effect came as an outcome of the changes that occurred in the level of improvement in credit risk management, which is in turn resulted from changes in the level of using Blockchain technology.